Rural and Indigenous women empowerment through productive groups and social microbusinesses in Mexico - Robinson Trápaga, Diana Gabriela (My University, 2019)
The organization of indigenous and rural women in productive and micro-enterprise groups aims to be a tool of empowerment, fighting against poverty and gender equity, with the three Sustainable Development Objectives of the 2030 Development Agenda of the United Nations. In Mexico, these objectives are addressed from the National Development Plan (2013-2018), in which gender is also established as a transversal strategy to be applied in the design and implementation of sector policies, programs and budgets. In this sense, it is established as a priority to address the social lag of the population, especially minorities. The objective of this article is to show the relationship between the empowerment of rural and indigenous women through their participation in productive projects and social micro-enterprises. The research is conducted using a descriptive methodology with documentary design, based on a literature review of publications that relate both concepts. As a result of the research, an integrative process is proposed towards the empowerment of rural and indigenous women who participate in productive projects or social micro-enterprises in Mexico. It is concluded that accompaniment, empathy and training are required to create social micro-enterprises that foster transformation, and social value and contribute to the local development.
Keywords: Empowerment; Productive groups; Social microbusiness; Microcredits; Campus Ensenada